2013
DOI: 10.1080/15427528.2013.795205
|View full text |Cite
|
Sign up to set email alerts
|

1-Aminocyclopropane-1-Carboxylate Oxidase 2 Reduction Effects on Physical and Physiological Responses of Eksotika Papaya

Abstract: The Malaysian Eksotika papaya (Carica papaya L.) has poor keeping quality due to its fast ripening attribute, which leads to post-harvest losses. This study is aimed at extending the shelf life of this perishable Eksotika fruit using antisense technology. A total of 6,000 Eksotika somatic embryogenic calli was transformed with the antisense 1aminocyclopropane-1-carboxylic acid oxidase 2 gene (ACO2) construct, and 46 PCRpositive putative transformants were obtained. Gene expression analysis using real-time PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Genomic DNA of the selected transformants was isolated from L. starkeyi cell pellets using the procedure described previously [ 16 ]. Transgene copy number was estimated using a real-time qPCR method described by Weng et al [ 32 ], which had been used in numerous studies [ 33 35 ] and is described in our recent publication [ 16 ]. Briefly, the target gene (X) copy number was calculated versus the reference gene (R) by X o /R o .…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA of the selected transformants was isolated from L. starkeyi cell pellets using the procedure described previously [ 16 ]. Transgene copy number was estimated using a real-time qPCR method described by Weng et al [ 32 ], which had been used in numerous studies [ 33 35 ] and is described in our recent publication [ 16 ]. Briefly, the target gene (X) copy number was calculated versus the reference gene (R) by X o /R o .…”
Section: Methodsmentioning
confidence: 99%
“…Real-time quantitative PCR (qPCR) has been widely used to determine gene copy number in engineered organisms [ 65 , 66 ]. In this study, the copy number of expressed chimeric cbh1 and eg2 genes in the transformants were estimated according to a method described by Weng et al [ 59 ], which has been used in numerous studies [ 66 68 ]. For comparison, the endogenous eukaryotic initiation factor 5 (eif5) gene was used as a single-copy reference gene [ 69 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 1990, MARDI started the research on delayed ripening papaya with the successful development of a tissue culture regeneration and transformation system, and identification of 1-aminocyclopropane-1-carboxylic acid oxidase 2 ( ACO 2) gene associated with ripening. Following which, transgenic and silencing technologies were used to develop new Eksotika papaya variety with delayed fruit ripening trait by manipulating the ACO 2 gene in the pathway ( Sekeli et al, 2013 ). The research findings showed ethylene production was greatly reduced by manipulating ACO 2 gene using antisense technique.…”
Section: Long-term Strategymentioning
confidence: 99%